Blended Learning Models in the Post-Pandemic Era: Redefining Classroom Instruction and Online Learning Integration - Suryaningsih Suryaningsih; Yassine Belhassen (Yayasan Adra Karima Hubbi, 2024)
BackgroundThe COVID-19 pandemic has catalyzed a significant shift in education, highlighting the need for flexible learning environments. As educational institutions transition to post-pandemic settings, blending traditional classroom instruction with online learning has become essential. Service learning, which combines community service with academic instruction, offers an innovative approach to enhance student engagement and learning. Integrating service learning into blended learning models can provide students with real-world experiences while developing both cognitive and social skills. ObjectiveThis study aims to explore how integrating service learning into blended learning models can redefine classroom instruction and online learning in the post-pandemic era. Specifically, it investigates the effectiveness of this integration in fostering student engagement, critical thinking, and civic responsibility. MethodologyA mixed-methods approach was employed, involving a survey of 300 students and interviews with 20 instructors from five universities. Data were analyzed to assess changes in students' cognitive and social skills, as well as their perceptions of the integration of service learning with blended learning formats. ResultsThe findings show that students in the integrated service learning and blended learning model demonstrated increased engagement, improved problem-solving skills, and greater awareness of social issues. Furthermore, instructors reported positive experiences in combining both instructional methods. ConclusionIntegrating service learning with blended learning models significantly enhances student engagement and learning outcomes in higher education. This approach is particularly valuable in the post-pandemic era, where flexible, hybrid learning environments are essential.